Investigation of traffic adaptation based interference alignment for cognitive radio networks - Heng DONG; Rong-fang SONG (Tongxin xuebao)
A novel method of adaptive interference alignment (IA) was proposed for cognitive radio networks. The new IA scheme, which was chiefly characterized by off-line feasible set optimization and traffic load oriented adaptation, en-ables dynamic sharing of channel resource among a pair of primary users and multiple pairs of secondary users. To effec-tively construct the beam-forming and interference suppression matrix for IA, then not only derive an adaptive closed-form algorithm, but its average degrees of freedom (d.o.f) were also analyzed with random traffic load model and a lower bound is given as well. The analysis is verified with statistic model simulation and the results show that the new method outperforms both modified opportunistic IA and fixed IA in average d.o.f and thus can significantly improve the sum capacity of cognitive users without introducing interference to the primary user. Moreover, due to its simplicity, the scheme is highly desirable to implement in low cost terminals.